Thermodynamic binding properties of a novel umami octapeptide K1ADEDSLA8 and its mutational variants p.A2G, p.D5E, and p.A2G+p.D5E (BMP) in complex with the umami receptor hT1R1/hT1R3 - Andac, Cenk A.; Ozel, Cem; Rababah, Taha M.; Kececiler-Emir, Ceren; Koklu, Kevser; Tekdas, Duygu Aydin; Yucel, Sevil (ELSEVIER SCI LTD, 2025)
Umami taste properties of a novel octameric peptide K(1)ADEDSLA(8) and its mutants p.A2G, p.D5E, and BMP (KGDEESLA, beef meaty peptide) were assessed by molecular docking, and molecular dynamics (MD) (>1 mu sec), MM-PBSA, and Mutational Affinity Prediction (MAP) methods. 3D-structure of the human umami taste receptor (hT1R1/hT1R3) was homology modeled and refined MD. Docking studies yielded three primary binding sites (PBS) for K(1)ADEDSLA(8) and BMP, one on hT1R1 and two on hT1R3. Upto 1200 nsec of MD studies revealed that K(1)ADEDSLA(8) binds only to Venus Flytrap Domains (VFTD) region of hT1R1 at high affinity (Delta G(o) = -11.94 kcal/mol), while BMP does not exhibit affinity towards hT1R1/hT1R3 in the absence of glutamate. MAP analysis for p.A2G (Delta G(o) = -7.77 kcal/mol) and p.D5E (Delta G(o) = -2.88 kcal/mol) strongly suggest that A(2) and D-5 in KA(2)DED(5)SLA increase the affinity and specificity of binding, posing great potential for the development of a novel umami peptide in future studies.
Keywords: Umami peptide; Molecular docking; Molecular dynamics; MM-PBSA; Mutational affinity prediction (MAP); T1R1/T1R3; MONOSODIUM GLUTAMATE; MOLECULAR-DYNAMICS; ENHANCING PEPTIDES; MAMMALIAN SWEET; TASTE; DOCKING; MECHANISM; ACCURACY; Chemistry; Food Science & Technology; Nutrition & Dietetics